A clinical and histopathological profile of patients with cutaneous tuberculosis - Neerja Puri (Wolters Kluwer Medknow Publications, 2011)
Extrapulmonary tuberculosis constitutes about 10% of all cases of tuberculosis, and cutaneous tuberculosis makes up only a small proportion of these cases. Despite prevention programs, tuberculosis is still progressing endemically in developing countries. Commonest clinical variant of cutaneous tuberculosis in our study was lupus vulgaris seen in 55% patients followed by scrufuloderma seen in 25% patients followed by orificial tuberculosis, tuberculosis verrucosa cutis, papulonecrotic tuberculid, and erythema induratum seen in 5% each. The commonest site of involvement was limbs seen in 50% patients followed by neck seen in 25% patients, face in 15%, and trunk in 10% patients. Maximum percentage of patients (55%) had duration of cutaneous tuberculosis between 6-12 months followed by 35% between 13-24 months, 5% had duration of cutaneous tuberculosis less than 6 months, and the rest 5% had duration more than 24 months. The commonest histopathological feature in our study was tuberculoid granuloma with epitheloid cell and Langhans giant cells seen in 70% patients, hyperkeratosis was seen in 15% patients and AFB bacilli were seen in 5% patients.